Cultural Memory and Historical Continuity: Reinterpreting Pre-Modern Texts in Contemporary Society - Aries Purwanto; Muh Irfan Mukhlishin; Indah Wahyuni; Emma Clark (Journal of Humanities Research Sustainability, 2026)
Background. Pre-modern texts constitute a foundational archive of cultural memory through which societies transmit values, identities, and historical consciousness across generations. In contemporary society, these texts are increasingly reinterpreted to address present concerns, revealing dynamic interactions between historical continuity and modern cultural frameworks. Purpose. This study aims to examine how cultural memory embedded in pre-modern texts is reinterpreted in contemporary contexts and how such reinterpretations contribute to the negotiation of historical continuity and social meaning. Method. The study employs a qualitative interpretative approach using textual and contextual analysis informed by cultural memory studies, hermeneutics, and historical criticism. Selected pre-modern texts and their contemporary reinterpretations are analyzed through close reading to identify shifts in meaning, narrative emphasis, and cultural function. Results. The findings indicate that contemporary reinterpretations do not merely preserve pre-modern texts but actively reframe them to respond to current social, ethical, and cultural challenges. Cultural memory functions as a selective and adaptive process, enabling continuity while allowing reinterpretation, transformation, and critique of inherited traditions. Conclusion. This study concludes that the reinterpretation of pre-modern texts plays a crucial role in sustaining historical continuity by transforming cultural memory into a living resource. Such processes reaffirm the relevance of historical texts in contemporary society while reshaping collective understanding of the past.